The trumpet of the swan - White, E. B. (Elwyn Brooks), 1899-1985 (HarperCollinsPublishers, 2000)
Louis, a voiceless Trumpeter swan, finds himself far from his wilderness home when he determines to communicate by learning to play a stolen trumpet.